Level of understanding the application of maqasid shariah in family Takaful products in Takaful Malaysia among UiTM Puncak Alam students / Afiqah Nur Syazlyn Mohd Hanapi - Mohd Hanapi, Afiqah Nur Syazlyn (2019)
Takaful is its own financial instrument. It is the foundation of Islamic insurance and its presence in the field of conventional banking and finance today is an alternative to the current secular insurance. The presence of takaful has raised numerous questions, including the extent to which maqasid shariah is used in all items that are either family or general takaful. The same is true of the takaful system, which follows the co-operative, supportive, and conscientious values of Islamic takaful between participants and takaful operators. The goal of this research is to study the extent to which the Family Takaful products offered in Takaful Malaysia as one of the largest takaful companies in Malaysia meet the maqasid shariah in terms of the participants ' social, political, academic, cultural and material heritage and to define the degree of understanding of the Diploma students in Muamalat Part 5. The method used for this research is quantitative which is using questionnaire and the scope of the survey is students Diploma Muamalat Part 5. Thus, to analyse this research Statistical Package for Social Science (SPSS) Version 17.0 is used to measure the validity. The descriptive analysis and content of reading material and relevant supporting standard.